2024
DOI: 10.3390/foods13050662
|View full text |Cite
|
Sign up to set email alerts
|

Germination: A Powerful Way to Improve the Nutritional, Functional, and Molecular Properties of White- and Red-Colored Sorghum Grains

Cagla Kayisoglu,
Ebrar Altikardes,
Nihal Guzel
et al.

Abstract: This study explored the effects of the germination of red and white sorghum grains (Sorghum bicolor [Moench (L.)]) for up to seven days on various properties of the grain. Germination enriched sorghum’s nutritional and sensory qualities while mitigating existing anti-nutritional factors. The study employed Fourier-transformed infrared spectroscopy (FT-IR) and scanning electron microscopy techniques to support its findings. Germination increased protein and lipid content but decreased starch content. White sorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Sprouting is an effective method of enhancing the edible value of grains and coarse cereals, and it can improve the culinary characteristics and sensory quality of foods [9]. A series of complex physiological and biochemical reactions occur during seed sprouting, wherein the stored nutrients such as starch and proteins are degraded [10], γ-aminobutyric acid and phenolic compounds are synthesized [11,12], antinutritional factors such as phytic acid are reduced [13], and the nutritional value of the grain and coarse cereal is increased to a certain extent, with improvement in taste. Some studies have reported on the nutritional value and functional properties of sprouted buckwheat.…”
Section: Introductionmentioning
confidence: 99%
“…Sprouting is an effective method of enhancing the edible value of grains and coarse cereals, and it can improve the culinary characteristics and sensory quality of foods [9]. A series of complex physiological and biochemical reactions occur during seed sprouting, wherein the stored nutrients such as starch and proteins are degraded [10], γ-aminobutyric acid and phenolic compounds are synthesized [11,12], antinutritional factors such as phytic acid are reduced [13], and the nutritional value of the grain and coarse cereal is increased to a certain extent, with improvement in taste. Some studies have reported on the nutritional value and functional properties of sprouted buckwheat.…”
Section: Introductionmentioning
confidence: 99%